TAX HEAVENS PHENOMENON: TAX PLANNING STRATEGY OR TAX AVOIDANCE - Dinik Fitri Rahajeng Pangestuti; Nisrina Sari; Ambar Lestari (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2020)
Abstract Tax planning is one example of the use of regulatory loopholes. On the other hand for the Fiscal Authority, carrying out tax avoidance practices as a form of tax planning will have a negative effect on the Government and, for this reason, the Government makes fiscal corrections as its remedial. Many also hide their assets in tax heavens countries. This is so that the assets they have are not taxed. Tax heavens countries are usually small countries that apply very low taxes, some even do not impose taxes at all. However, the government has prepared an Automatic Exchange of Information (AEoI) data exchange plan that occurs in 2018, certainly will make tax evaders unable to run away from the pursuit of the tax authorities, even if they have to flee to tax heavens countries (tax heavens). Keywords: tax heavens, tax planning, Automatic Exchange of Information (AEoI) Abstrak Perencanaan pajak adalah salah satu contoh penggunaan celah peraturan. Pada sisi lain bagi Otoritas Fiskal, melakukan praktik penghindaran pajak sebagai bentuk perencanaan pajak akan membawa efek negatif bagi Pemerintah dan, untuk itulah, Pemerintah melakukan koreksi fiskal sebagai remedialnya. Banyak juga yang menyembunyikan asetnya di negara-negara tax heavens. Hal ini bertujuan agar aset yang mereka punya tidak terkena pajak. Negara tax heavens biasanya merupakan negara kecil yang menerapkan pajak yang sangat rendah, bahkan ada yang tidak mengenakan pajak sama sekali. Namun, pemerintah telah menyiapkan Rencana pertukaran informasi data perbankan secara otomatis (Automatic Exchange of Information/AEoI) yang terjadi pada 2018, dipastikan akan membuat para pengemplang pajak tidak akan bisa lari dari kejaran otoritas pajak, sekalipun mereka harus kabur ke negara surga pajak (tax heavens). Kata kunci: Tax Heavens, Tax Planning, Automatic Exchange of Information (AEoI)